Expectant parents’ experiences of parental education within the antenatal health service - Norling-Gustafsson, Ann (Dove Medical Press, 2011)
Being an expectant parent is a life changing event and it is something that most people will experience in their lifetime. Many people who are parents for the first time will participate in parenting education. Most of the previous studies associated with parenting education focus on subjects such as birth outcome and breastfeeding. The purpose of this study is to focus on the less investigated aspect of the parents’ experience of participating in parenting education with Maternal Healthcare Services (MVC). A qualitative, phenomenological, hermeneutical method was selected to be used to analyze our findings and we used the statements of twenty participants to accumulate enough material to develop it into twelve sub-themes and five themes. The results of this study show that these expectant parents had few or no expectations of the parenting education that they were going to participate in. Generally speaking the parents seemed to be satisfied with the program. They described their reasons for participating as a chance to get together with other people in similar circumstances and to share information and they found a midwife to be a trustworthy professional person to confirm the information that was available to them from other sources.